2019
DOI: 10.21595/jve.2019.20781
|View full text |Cite
|
Sign up to set email alerts
|

Fault diagnosis method for energy storage mechanism of high voltage circuit breaker based on CNN characteristic matrix constructed by sound-vibration signal

Abstract: Aiming at the problem that some traditional high voltage circuit breaker fault diagnosis methods were over-dependent on subjective experience, the accuracy was not very high and the generalization ability was poor, a fault diagnosis method for energy storage mechanism of high voltage circuit breaker, which based on Convolutional Neural Network (CNN) characteristic matrix constructed by sound-vibration signal ,was proposed. In this paper, firstly, the morphological filtering was used for background noise cancel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…(1) Local response normalization [26] is the most common algorithm in CNNs. e response value is calculated by…”
Section: Cnn In DLmentioning
confidence: 99%
“…(1) Local response normalization [26] is the most common algorithm in CNNs. e response value is calculated by…”
Section: Cnn In DLmentioning
confidence: 99%
“…Numerous studies have shown that mechanical faults are one of the main problems influencing the operational reliability of the circuit breaker (CB) [3][4][5]. In order to monitor the status and realize a fault diagnosis of the CB, the commonly used acquisition signals may include transient electric field [6], vibration signal [7][8][9][10], current signal [9][10][11], sound signal [12], and travel-time curve [13,14]. Among them, the use of vibration signals for CB fault diagnosis has the advantages of low cost and high diagnosis performance.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the effectiveness of machine learning-based sensor fusion has been demonstrated in circuit breaker fault detection and classification. Recent studies have combined various signals for diagnosis, including vibration and sound [31], coil current and angular displacement [32], coil current and sound [33], vibration, temperature, and travel curve [34], and vibration and coil current [35]. The success of sensor fusion in circuit breaker fault detection and its robustness against noise [36] suggest its potential application to the arc duration measurement in the substation environment, which is largely unexplored.…”
Section: Introductionmentioning
confidence: 99%